2017
DOI: 10.11648/j.mc.20170504.11
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Physicochemical and Thermal Properties of Energy of Consciousness Healing Treated Ferrous Sulphate Using PXRD, PSD, DSC, and TGA/DTG Analysis

Abstract: Abstract:Ferrous sulphate is an inorganic salt of iron used to treat iron deficiency anaemia and maintain the overall health in our body. The current study was designed to evaluate the impact of The Trivedi Effect ® -Energy of Consciousness Healing Treatment on the physicochemical and thermal properties of ferrous sulphate using PXRD, PSA, DSC, and TGA/DTG analysis. Ferrous sulphate test item was divided into two parts, one part was considered as control (without Biofield Energy Treatment), whereas the second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…There are several researchers who have conducted research on the benefits of rice husk ash, have mixed rice husk ash into mortar with a composition of 10% rice husk ash which has high compressive strength and splitting compressive strength, so they concluded that rice husk ash can improve physical and mechanical properties [3]. Rice husk ash has been used as a cement mixture to increase the strength of concrete [4].…”
Section: Introductionmentioning
confidence: 99%
“…There are several researchers who have conducted research on the benefits of rice husk ash, have mixed rice husk ash into mortar with a composition of 10% rice husk ash which has high compressive strength and splitting compressive strength, so they concluded that rice husk ash can improve physical and mechanical properties [3]. Rice husk ash has been used as a cement mixture to increase the strength of concrete [4].…”
Section: Introductionmentioning
confidence: 99%